Soekarno’s Strategic Leadership For The World (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strategic leadership is a competence in formulating the strategy, mission and strategic substance of an organization, accompanied by the ability to execute and implement policies and strategic decisions in accordance with the ongoing environmental growth review of an internal team that is powerful and driven to accomplish future objectives. Indonesian proclaimer and founding father, Ir. Sukarno is an example of a leader who has exhibited strategic leadership qualities that have been tested at the national and international levels. Soekarno, as the first President of the Republic of Indonesia, has taken part in a variety of foreign positions in Southeast Asia, America and Russia, particularly in the start of the Non-Aligned Movement (NAM), the Asia-Africa Summit and many others. Soekarno is commonly used as the name of the main street in different countries so that he deserves to be the world's strategic king. This study employs a qualitative approach with socio-historical interpretation to uncover strategic leadership concepts that have ever been put out in the foreign community.